SEX, FEMINISM AND SEXUAL REVOLUTION - Michael M. Uzomah; Titi Christiana Falana (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This paper is an expository analysis of sex, feminism and sexual revolution. The paper reveals that right from historic time, the society’s normative pedagogy has been overwhelmingly influenced by obsessive religious sexual morality. Fundamentalist sexual morality is arguably a morality and pedagogy that is economical with the truth about the nature, meaning and essence of sex. It was a regime that mystified and forged ossified myths that confounded the meaning and essence of sex. It was a regime that hid the truth or presented a narrow notion of the primary purpose of sex. Worse still, it denied children and impressionable adolescences the knowledge of sex for fear that they may be corrupted.  Consequently, children resorted to other ‘honest and open’ means for the knowledge of sex. Subsequently, armed with the true knowledge of sex when the children of yesterday grew into adolescence and adulthood, they revolted against the traditional order. The strict and dishonest traditional normative pedagogy inadvertently precipitated the sustained resentment that eventually snowballed into full scare sexual revolution in a free and liberated society fostered by the emergence of information technology. Based on the findings of the analysis, the paper argues that although, sex is a profoundly close and personal affair, yet, it is an act of man and human act and must be subjected to ethical reckoning based on the fact that it also has a social dimension arising from the rational and gregarious nature of humans. While we do not totally subscribe to the list of non-traditional sexual behaviours which include senseless and irrational pervasions, we also do not believe that morally accepted sexual behaviours should be limited to traditional sexual behaviours as classically delineated by society under repressive religious influence. The paper concludes that the notion that reproduction is the only primary purpose of sex is miss-guided. Individuals must be allowed significant deal of sexual freedom, however, with responsibility. The paper advocates for a sexual freedom that is necessarily accompanied by emotional intelligence, self-discipline and a conscious resolve not to harm significant others and the society.